A preliminary study on the effects of substituting fishmeal with defatted black soldier fly (Hermetia illucens) larval meal on Asian seabass (Lates calcarifer) juveniles: Growth performance, feed efficiency, nutrient composition, disease resistance, and economic returns - Liu, Yun; Andin, Victor Charlie; Chor, Wei-Kang; Gunasekaran, Baskaran; Chong, Chou-Min; Lee, Po-Tsang; Loh, Jiun-Yan (John Wiley and Sons Inc, 2024)
This study aims to develop an alternative aquafeed derived from insect meal for Lates calcarifer juveniles, with the objectives of exploring the physiological performance, biological parameters, and economic analysis of substituting fishmeal (FM) with defatted black soldier fly (Hermetia illucens) larvae (BSFL) as part of the diet of L. calcarifer juveniles. Five practical diets were formulated to include 0% (BSFL0, serves as control group), 5% (BSFL5), 10% (BSFL10), 15% (BSFL15), and 20% (BSFL20) of BSFL meal, partially or fully replacing FM, respectively. Each diet was randomly assigned to triplicate groups of 30 fish (10.70 ± 0.07 g) per tank (300 L). The fish were fed twice daily to apparent satiation. A 56-day feeding trial was conducted to evaluate the impacts of defatted BSFL meal replacing FM on the growth performance, feed efficiency, composition analysis of fish muscle, cumulative mortality rate challenged with Vibrio parahaemolyticus, and economic returns of L. calcarifer. These results show that differences in weight gain and specific growth rate among the different treatments were statistically significant (p < 0.05), except for the absence of significant variation (p < 0.05) between BSFL0 and BSFL5, and followed by BSFL10 > BSFL0 > BSFL5 > BSFL15 > BSFL20. However, the feed conversion ratio and protein efficiency ratio showed the opposite trend as above. Although the diets experienced a decline in crude protein content and an increase in crude fat content with the increasing proportion of BSFL substituting FM, the crude protein and fat content of fish muscle were only slightly influenced. It is worth mentioning that levels of nonessential amino acids, delicious amino acids, saturated fatty acids, omega-6, omega-9 in BSFL10 group all showed an increase compared with the control group. After a 7-day challenge test with V. parahaemolyticus, the cumulative mortality rates of the BSFL5 and BSFL10 groups, respectively, dropped to 5.20%, 5.28% compared to the control group's 16.88%; however, the mortality rates of BSFL15 (34.67%) and BSFL20 (41.77%) groups were found to be significantly (p < 0.05) increased. From an economic perspective, the incidence cost for each experimental group showed a trend as BSFL10 < BSFL0 < BSFL5 < BSFL15 < BSFL20, whereas the profit index in each treatment exhibited the opposite trend as above. It was concluded that low (5%) or moderate (10%) levels of BSFL substituting FM in aquaculture feed could improve the physiological performances, disease resistance, and economic returns of L. calcarifer. However, excessive substitution (>15%) leads to a negative effect. From an economic point of view, 10% inclusion of BSFL in practical diets is recommended for L. calcarifer juveniles.